The Implementation Of Project Based Learning Models To Improve Students Speaking Skills - M Abdul Aziz; Moh Zainuddin; Khoirul Wafa; M Abdul Aziz; Moh Zainuddin; Khoirul Wafa (INTENS (International Journal of English Education and Linguistics), 2024)
Project-Based Learning is a learning approach that involves students in comprehensive projects that lead to public outputs such as products, publications, or presentations. Speaking skills play a crucial role in enhancing students' communicative abilities. By mastering speaking skills, students can critically understand the learning material. However, based on observations at SMP Negeri 4 Bojonegoro, students' speaking skills are still relatively low. This research aims to determine whether the implementation of the Project-Based Learning model can improve students' speaking skills. The research uses the Classroom Action Research (CAR) method and is conducted in three cycles. Data is collected through tests, observations, and interviews. Tests are used to measure students' speaking skill performance, observations are used to understand the implementation of Project-Based Learning during the teaching process. The research results show that students' speaking skills improved from one cycle to the next. In cycle I, the average score of students was 66.125, in cycle II, it increased to 72.875, and in the subsequent cycle III, it further increased to 75.25. Meanwhile, the observation results from the pre-test were only 49%, whereas in the final post-test, a score of 81% was obtained. it can be inferred that the Project-Based Learning model enhances students' speaking skills.